2016
DOI: 10.1002/uog.15735
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of cobblestone lissencephaly associated with Walker–Warburg syndrome based on a specific sonographic pattern

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 8 publications
2
25
0
1
Order By: Relevance
“…Advances in ultrasonography may change this limitation, and two recent publications have suggested that improved diagnostic accuracy with ultrasound is possible. 11,12 Our present study lends support to that suggestion, as the 3/23 (13%) fetuses with lissencephaly did not have the diagnosis made on ultrasonography, although borderline ventriculomegaly was found in 1 case. The inability to detect (or raise the possibility of) lissencephaly on ultrasound, coupled with the rarity of the disorder (prevalence approximately 1 : 100000), makes it virtually impossible to perform a prospective study of diagnostic accuracy of antenatal imaging methods in de novo cases.…”
Section: Full Paper: Iumr For Lissencephaly Bjrsupporting
confidence: 86%
“…Advances in ultrasonography may change this limitation, and two recent publications have suggested that improved diagnostic accuracy with ultrasound is possible. 11,12 Our present study lends support to that suggestion, as the 3/23 (13%) fetuses with lissencephaly did not have the diagnosis made on ultrasonography, although borderline ventriculomegaly was found in 1 case. The inability to detect (or raise the possibility of) lissencephaly on ultrasound, coupled with the rarity of the disorder (prevalence approximately 1 : 100000), makes it virtually impossible to perform a prospective study of diagnostic accuracy of antenatal imaging methods in de novo cases.…”
Section: Full Paper: Iumr For Lissencephaly Bjrsupporting
confidence: 86%
“…Recently, Lepais et al (2015) reported two siblings affected with ALG3-CDG presenting antenatally with short long bones, IUGR, and cerebellar vermis hypoplasia. Defects of protein O-mannosylation (POMT) are responsible for autosomal recessive Walker-Warburg syndrome (POMT1/ POMT2-CDG) and muscle-eye-brain disease (POMGNT1-CDG) (Wopereis et al 2006 ;Lacalm et al 2016). They are suspected by ultrasound findings and pathological examination, but their diagnosis relies on mutation analysis of the corresponding genes: POMT1, POMT2,andPOMGnT1.…”
Section: Congenital Disorders Of Glycosylationmentioning
confidence: 99%
“…The formation of an extracortical agyric neuroglial layer occurs. It seems that the primary cause is the deficit of glycosylation of dystroglycans, resulting in neuroglial overmigration [44][45][46][47][48][49][50].…”
Section: Cortical Formation Abnormalitiesmentioning
confidence: 99%